Efficiency of defects formation in spinel under high energy electron and gamma beam irradiation - Gokov, S.P.; Gritsyna, V.T.; Kasilov, V.I.; Kochetov, S.S.; Kazarinov, Yu.G. (Вопросы атомной науки и техники, 2009)
There were provided the comparative investigations of the efficiency of optical absorption centers formation in magnesium aluminates spinel (single crystals and ceramics) at the influence of high energy gamma or electron beams. It was revealed that at gamma irradiation in the single crystals and ceramics the most probably the hole centers are formed which were created primarily at growth defects: cationic vacancies and anti-site defects. After electron irradiation of different fluences in absorption spectra there were observed bands related to hole centers (defects in the cationic sub-lattice) which practically does not change, while the concentration of electron centers (defects in the anion sub-lattice) grows proportionally to the electron fluence.